THE INFLUENCE OF GROUP INVESTIGATION ON THE ABILITY OF CRITICAL THINKING AND SCIENTIFIC WRITING - Yuliana Sri Purbiyati (Widya Mandala Surabaya Catholic University, 2021)
This study describes the effect of implementing group investigation method on students' critical thinking and the completion of assignments in setting background abilities. This research method is descriptive by applying the group investigation learning method to the Indonesian Language course with eight steps, namely the focus of learning, selecting topics, planning in groups, implementation, analysis and synthesis, presentation of results in front of the class, evaluation, and assessment. As for the research subjects, there were 70 students being in the second semester of the 2019-2020 academic year in the Accounting Study Program at Darma Cendika Chatolic University, Surabaya. The conclusion of this study was that there was a significant effect on the implementation of the group investigation learning method on the critical thinking ability of 85.5% and on the completion of the task of compiling the background by 48.64%.